Collaborative strategic reading in ESP classrooms: its association with reading comprehension across two proficiency levels - Wandira, Septiana; Nur Hadiyansah, Dwi (Universitas PGRI Adi Buana Surabaya, 2026)
This study examined the association between Collaborative Strategic Reading (CSR) strategy use and reading comprehension among English for Specific Purposes (ESP) students at different English proficiency levels. Using a quantitative, non-experimental design, the study involved 45 ESP students selected through total sampling. Data were collected through a CSR Strategy Use Questionnaire and a Reading Comprehension Test and analyzed using descriptive statistics, Pearson correlation, independent samples t-test, and moderation regression analysis in SPSS. The findings revealed a statistically significant and very strong positive association between CSR strategy use and reading comprehension (r = 1.00, p < .001), indicating that students who reported greater use of CSR strategies achieved higher reading comprehension scores. The independent samples t-test showed a significant difference in reading comprehension between proficiency groups, with high-proficiency students outperforming low-proficiency students (t = 8.54, p < .001). However, the moderation analysis demonstrated that English proficiency did not significantly moderate the relationship between CSR strategy use and reading comprehension (p > .05). These findings suggest that the use of CSR strategies is strongly associated with reading comprehension among ESP students. In contrast, English proficiency remains an important factor influencing overall reading performance. The study contributes to the understanding of reading strategy use in ESP contexts and supports the value of CSR in enhancing reading comprehension across proficiency levels.